Binding and Conversion of Selenium in Candida utilis ATCC 9950 Yeasts in Bioreactor Culture - Marek Kieliszek; Stanisław Błażejak; Eliza Kurek (Molecules, 2017)
Selenium is considered an essential component of all living organisms. The use of yeasts as a selenium supplement in human nutrition has gained much interest over the last decade. The accumulation and biochemical transformation of selenium in yeast cells is particularly interesting to many researchers. In this article, we present the results of the determination of selenium and selenomethionine content in the biomass of feed yeast Candida utilis ATCC 9950 obtained from the culture grown in a bioreactor. The results indicated that C. utilis cells performed the biotransformation of inorganic selenium(IV) to organic derivatives (e.g., selenomethionine). Selenium introduced (20–30 mg Se4+∙L−1) to the experimental media in the form of sodium(IV) selenite (Na2SeO3) salt caused a significant increase in selenium content in the biomass of C. utilis,irrespective of the concentration. The highest amount of selenium (1841 μg∙gd.w.−1) was obtained after a 48-h culture in media containing 30 mg Se4+∙L−1. The highest content of selenomethionine (238.8 μg∙gd.w.−1) was found after 48-h culture from the experimental medium that was supplemented with selenium at a concentration of 20 mg Se4+∙L−1. Biomass cell in the cultures supplemented with selenium ranged from 1.5 to 14.1 g∙L−1. The results of this study indicate that yeast cell biomass of C. utilis enriched mainly with the organic forms of selenium can be a valuable source of protein. It creates the possibility of obtaining selenium biocomplexes that can be used in the production of protein-selenium dietary supplements for animals and humans